2008
DOI: 10.1002/jbm.b.31175
|View full text |Cite
|
Sign up to set email alerts
|

In vivo murine model of continuous intramedullary infusion of particles—A preliminary study

Abstract: Continued production of wear debris affects both initial osseointegration and subsequent bone remodeling of total joint replacements (TJRs). However, continuous delivery of clinically relevant particles using a viable, cost effective, quantitative animal model to simulate the scenario in humans has been a challenge for orthopaedic researchers. In this study, we successfully infused blue-dyed polystyrene particles, similar in size to wear debris in humans, to the intramedullary space of the mouse femur for four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Ren et al [49] using in vivo bioluminescent imaging showed systemic trafficking of macrophages to PMMA particles injected into the mouse femoral shaft. Macrophages were also found to migrate to sites with UHMWPE injection: this has been shown using either a single bolus of UHMWPE particles in the femoral shaft [50] or using a continuous infusion of UHMWPE particles through a micro-diffusion pump [22,51,52], a more clinically relevant model. The next step was to link in vivo MCP-1 secretion and macrophage recruitment in the presence of particles.…”
Section: Interfering With Ongoing Migration Ofmentioning
confidence: 97%
“…Ren et al [49] using in vivo bioluminescent imaging showed systemic trafficking of macrophages to PMMA particles injected into the mouse femoral shaft. Macrophages were also found to migrate to sites with UHMWPE injection: this has been shown using either a single bolus of UHMWPE particles in the femoral shaft [50] or using a continuous infusion of UHMWPE particles through a micro-diffusion pump [22,51,52], a more clinically relevant model. The next step was to link in vivo MCP-1 secretion and macrophage recruitment in the presence of particles.…”
Section: Interfering With Ongoing Migration Ofmentioning
confidence: 97%
“…Male and female BALB/cByJ mice (8–12 weeks old) were used for the continuous femoral intramedullary polyethylene particle infusion model as previously described ( Figure 1A ) ( Ma et al, 2009 ; Lin et al, 2016 ; Pajarinen et al, 2017 ). Briefly, the mouse was administered with preoperative analgesia (0.1 mg/kg of buprenorphine, subcutaneously) and inhalation anesthesia (2% isoflurane in 100% oxygen, 1 L/min) on a warm animal surgery station.…”
Section: Methodsmentioning
confidence: 99%
“…The animals were kept in a room at 24℃, 50% humidity, and with a 12 h light/dark cycle (light from AM 7:00 to PM 7:00). The animals were randomly separated into four groups: (1) sham group (n = 8) (underwent surgery only) (2) vehicle group (n = 8) (implanted with PS particles) [36][37][38], (3) WDL 4w (n = 8, implanted with PS particles and treated with WDL for 4 weeks. 7 animals remained at the end of the experiment) and (4) WDL 8w (n = 8, treatment for 8 weeks).…”
Section: Establishing the Calvarial Particle-induced Osteolysis Modelmentioning
confidence: 99%
“…However, considerable time was spent preparing enough wear debris for these animal models, while polystyrene (PS) particles are readily available and are widely used both commercially and for biomedical research [59,60]. PS particles have been used in many animal studies to create particle-induced osteolysis animal models [36][37][38]. Furthermore, given that the size distribution and shape of PS particles are easier to control, this study used PS particles for the animal model.…”
Section: Et Al Also Indicated That Traditional Mixed Extracts Of Medi...mentioning
confidence: 99%